Patient satisfaction with peri-operative anesthesia care and associated factors at two National Referral Hospitals: a cross sectional study in Eritrea - Yonatan Mehari Andemeskel; Traudl Elsholz; Ghidey Gebreyohannes; Eyasu H. Tesfamariam (BMC, 2019)
Abstract Background Measuring patient satisfaction has become an important parameter of the continuous quality assessment and improvement in anaesthesia services. The aim of this study was to assess the level of patient satisfaction with perioperative anaesthesia care and to determine the factors that influence satisfaction. Method This study is an cross sectional design, conducted on 470 patients who underwent different types of surgeries at two National Referral Hospitals in Asmara, Eritrea between January and March of 2018. Patients were interviewed 24 h after the operation using a Tigrigna translated Leiden Perioperative Care Patient Satisfaction questionnaire (LPPSq). Descriptive and inferential analysis were made using SPSS (version 22). Statistical significance level was set at P < 0.05. Results The overall satisfaction score was 68.8%. Less fear and concern was observed among patients with satisfaction scores of 87.5%. Staff-patient relationship satisfaction score was 75%. Patients were least satisfied with information provision (45%). Multivariable analysis revealed that satisfaction of patients who did surgery at Halibet hospital is significantly higher (p < 0.001) than those patients who did at Orotta hospital. Moreover, those patients who did elective surgery had higher level of satisfaction that those who did emergency surgery (p < 0.001). Conclusion Moderate level of satisfaction was observed among the patients. Generally, the study emphasized that the information provision about anesthesia and surgery was low. Patients described better staff-patient relationship and low fear and concern related to anesthesia and surgery was observed.